2019
DOI: 10.1007/s10877-019-00377-x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the time of cerebral desaturation episodes and outcome in aneurysmal subarachnoid haemorrhage: a preliminary study

Abstract: In this preliminary study we investigated the relationship between the time of cerebral desaturation episodes (CDEs), the severity of the haemorrhage, and the short-term outcome in patients with aneurysmal subarachnoid haemorrhage (aSAH). Thirty eight patents diagnosed with aneurysmal subarachnoid haemorrhage were analysed in this study. Regional cerebral oxygenation (rSO 2) was assessed using near infrared spectroscopy (NIRS). A CDE was defined as rSO 2 < 60% with a duration of at least 30 min. The severity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…As the patient's brain tissue and cranial nerves have been damaged, it is necessary to repair the damaged nerve cells, re-establish nerve function, and promote the patient's recovery. Conventional care is now the usual clinical choice to restore consciousness, but with less than satisfactory results [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…As the patient's brain tissue and cranial nerves have been damaged, it is necessary to repair the damaged nerve cells, re-establish nerve function, and promote the patient's recovery. Conventional care is now the usual clinical choice to restore consciousness, but with less than satisfactory results [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, patients who were previously diagnosed with stroke or brain injury with chronic changes in CT, patients admitted with a diagnosis of brain death, and patients whose biomarker levels were related to diseases other than aSAH (cancer, severe kidney or liver disease, active or chronic inflammatory diseases) were excluded. Patients were treated based on standard SAH guidelines including early diagnosis, surgical clipping or coiling, and admission to the intensive care unit [17][18][19]. The choice of surgical treatment of the aneurysm was determined following a multidisciplinary discussion including vascular neurosurgeons and an interventional neuroradiologist depending on the location, size, and morphological features of the aneurysm; the presence of a mass effect caused by the aneurysm and/or an associated haematoma; the presence of multiple aneurysms; and the patient's neurological and general medical condition.…”
Section: Study Populationmentioning
confidence: 99%
“…Using the definition of cerebral desaturation of <50% for 30 min on either side, and poor outcomes as a mRS of 4–6, it was observed that cerebral desaturation was independently associated with poor functional outcomes at 3 months (OR 2.72, 95%CI 1.02–7.20) but not at 12 months. In a small study of 38 patients using a definition of cerebral desaturation of <60% for at least 30 min on either side, patients with an unfavorable outcome spent more time with a cerebral desaturation than those with a good outcome (5 h 43 vs. 1 h 47, p = 0.02) ( 61 ). Patients with episodes of cerebral desaturation lasting more than 2 h were at much higher risk of poor short-term outcomes than those without [OR 15.4 (95% CI: 1.1–214.2%)].…”
Section: Clinical Data—vasospasm DCI Prognosismentioning
confidence: 99%